2023
DOI: 10.1097/gox.0000000000004936
|View full text |Cite
|
Sign up to set email alerts
|

Closed Incision Negative Pressure Therapy in Oncoplastic Breast Surgery: A Comparison of Outcomes

Abstract: Background: We aim to discern the impact of closed incision negative pressure therapy (ciNPT) on wound healing in the oncoplastic breast surgery population. Methods: A retrospective analysis was conducted on patients who underwent oncoplastic breast surgery with and without ciNPT in a single health system over 6 years. Oncoplastic breast surgery was defined as breast conservation surgery involving partial mastectomy with immediate volume displacement or replacement techniques. Primary outcomes were rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Wound dehiscence has been shown to cause significant morbidity, including decreased patient quality of life, prolonged hospital stays, and increased care costs. 17,27,[31][32][33][34][35][36][37][38][39][40][41][42] Our finding is congruent with other studies examining ciNPWT in orthopedic trauma, 5,43 breast surgery, 11,14,15,44 abdominal wall reconstruction, 34,45 laparotomy, 46,47 ventral hernia repair, 48 and reviews combing multiple types of procedures. 36,41,45,[49][50][51][52] However, results in the literature are mixed, and other studies do not show this relationship.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Wound dehiscence has been shown to cause significant morbidity, including decreased patient quality of life, prolonged hospital stays, and increased care costs. 17,27,[31][32][33][34][35][36][37][38][39][40][41][42] Our finding is congruent with other studies examining ciNPWT in orthopedic trauma, 5,43 breast surgery, 11,14,15,44 abdominal wall reconstruction, 34,45 laparotomy, 46,47 ventral hernia repair, 48 and reviews combing multiple types of procedures. 36,41,45,[49][50][51][52] However, results in the literature are mixed, and other studies do not show this relationship.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies demonstrate a benefit on rates of seroma with the use of ciN-PWT, 11,41,44,49,50,52,54,55,63 but results are mixed. [6][7][8][13][14][15]33,45,48,61 Seromas develop as a result of the accumulation of serum in internal spaces. In vivo studies have shown improved fluid flow within 4 days of ciNPWT, resulting in decreased porcine subcutaneous dead spaces and therefore reduced risk of seroma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a surgeon may create a slight pyramid skin bridge at the T‐junction to decrease the tension at the T‐junction in higher BMI patients. Lastly, a surgeon may choose to use a closed incision negative pressure device on this higher‐risk patient population as an intraoperative dressing, which increases blood flow and decreases tension and; results in decreased wound complication and wound dehiscence rates 34 . It is also important to consider that patients with multiple co‐morbidities (chronic renal failure, obesity, smoking, significant cardiovascular disease) may not be appropriate candidates for an oncoplastic operation, and a shorter operation with a partial mastectomy alone may be a better, safer option.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, few studies have compared NPWDs with standard dressings in oncoplastic breast procedures [40,43,44].…”
Section: Discussionmentioning
confidence: 99%